AB0 blood group and prognosis in patients with pancreatic cancer - Rahbari, Nuh Nabi; Bork, Ulrich; Hinz, Ulf; Leo, Albrecht; Kirchberg, Johanna; Koch, Moritz; Büchler, Markus W.; Weitz, Jürgen (BMC cancer, 2012)
Although blood group 0 is associated with a reduced risk of pancreatic cancer, little is known about the role of AB0 blood group antigens in disease progression. We assessed the prognostic relevance of AB0 blood status in a large cohort of patients with resected pancreatic cancer.